2023
DOI: 10.3389/fpls.2023.1251418
|View full text |Cite
|
Sign up to set email alerts
|

Oolong tea cultivars categorization and germination period classification based on multispectral information

Qiong Cao,
Chunjiang Zhao,
Bingnan Bai
et al.

Abstract: Recognizing and identifying tea plant (Camellia sinensis) cultivar plays a significant role in tea planting and germplasm resource management, particularly for oolong tea. There is a wide range of high-quality oolong tea with diverse varieties of tea plants that are suitable for oolong tea production. The conventional method for identifying and confirming tea cultivars involves visual assessment. Machine learning and computer vision-based automatic classification methods offer efficient and non-invasive altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…The parameter optimization of GWO improves the model performance [39]; therefore, parameter optimization is necessary to build a high-accuracy rice variety classification model. This result is similar to that of Qiong Cao et al [40], who achieved the best performance with the GWO-optimized SVM model for the classification of oolong tea varieties with multispectral information and the classification of the germination stage, with similar classification results. This also further indicates that the GWO-optimized RF rice classification and identification model can perform well.…”
Section: Rf Classification Model Optimizationsupporting
confidence: 88%
“…The parameter optimization of GWO improves the model performance [39]; therefore, parameter optimization is necessary to build a high-accuracy rice variety classification model. This result is similar to that of Qiong Cao et al [40], who achieved the best performance with the GWO-optimized SVM model for the classification of oolong tea varieties with multispectral information and the classification of the germination stage, with similar classification results. This also further indicates that the GWO-optimized RF rice classification and identification model can perform well.…”
Section: Rf Classification Model Optimizationsupporting
confidence: 88%
“…Therefore, whether there are significant differences in parameters among plants cannot be used as the only criterion for elimination, and different characteristic parameters have different contributions and sensitivities in the determination of recognition objects. For example, through a continuous projection algorithm, Cao et al (2023) reported that among 27 spectral parameters, colour parameters played a more important role in the classification of 18 oolong tea cultivars and can be accurately divided into early, mesophytic, and late species, with a recognition accuracy of more than 90%.…”
Section: Discussionmentioning
confidence: 99%